DID THE 2004 CAP REFORM AFFECT PRODUCTION PRACTICES OF CEREALS? INSIGHTS FROM THE AGRICULTURAL INPUT SUPPLIERS - Theodoros MARKOPOULOS; Christos KARELAKIS; Konstantinos GALANOPOULOS; Konstadinos MATTAS (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The Mid-term review of the Common Agricultural Policy in 2003/2004 has strengthened the multifunctional role of agriculture by implementing “decoupling”, “modulation” and “cross-compliance” and created a number of significant changes in agricultural production in all EU member states. Specifically, the reform shifted emphasis away from commodity support towards environmental contracts, diversified production practices and rural development. In the case of cereals, a full decoupling was applied in subsidies and integration through rights in the Single Payment Scheme, except rice, which was one of the few crop cases in which part of the subsidy remained coupled, particular in countries with significant production like Greece. Within this context, the present study aims to analyze the impact that the reformed CAP measures had on agricultural production and more specifically variations in production diversification. The novelty of this study is that instead of focusing on the producers, it targeted the agricultural input stores, so as to get better insights of the CAP reform impacts on a larger scale of the regional economy. Accordingly, primary data were collected through personal interviews (structured questionnaire) from 209 owners of agricultural input stores in the region of Anatoliki Makedonia and Thraki and were analyzed through multivariate data analysis. The results identify important antecedents for the regional economy and the viability of agricultural input stores, which include factors of the reformed CAP, environmental issues, financial measures and CAP effects on cereal production and marketing.